(untitled) (Research, Society and Development, 2022)
The objective of this work was to develop a chutney with different proportions of blackberry, raspberry and strawberry, in order to preserve the fruit and ensure the flow of production. Seven chutney formulations were prepared following the simplex-centroid design, with different proportions of blackberry, raspberry and strawberry (F1 - 100% blackberry; F2 - 100% raspberry; F3 - 100% strawberry; F4 - 50% blackberry/50% raspberry; F5 - 50%raspberry/50% strawberry; F6 - 50% strawberry/50% blackberry and F7 - 33.33% blackberry/ 33.33% raspberry/ 33.33% strawberry). In the sauces, the physicochemical characteristics (soluble solids, water activity, pH, acidity, color and texture) and sensorial characteristics (acceptability and purchase intention) were determined. The highest values ​​for soluble solids were related to the presence of raspberry. The sauces were classified as highly acidic, with lower pH values ​​associated with the presence of blackberry and raspberry, with a tendency to increase as the proportion of strawberry was increased. The predominant color of the chutney was red, and the presence of strawberry was a factor that contributed to lighter sauces. The blackberry had little influence on the texture of the chutney, while the raspberry and the strawberry were the fruits responsible for increasing the consistency and viscosity of the product. Acceptability was positive for the seven formulations, with the highest acceptance associated with the formulation with equal parts of blackberry, raspberry and strawberry (F7). The development of a chutney with different proportions of blackberry, raspberry and strawberry is viable and can be an alternative for fruit flow.